2019
DOI: 10.1111/iwj.13095
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multidisciplinary foot care team on outcome of diabetic foot ulcer in term of lower extremity amputation at a tertiary care unit in Karachi, Pakistan

Abstract: To compare the outcomes of diabetic foot ulcers (DFU) in terms of healing and lower extremity amputation (LEA) rate before and after training of multidisciplinary foot care team (MDFCT). Subjects were categorised into two groups; Group‐A cases seen between 1997 and 2006 (before upgrading of training and services of MDFCT) and Group‐B cases seen between 2007 and 2016 (after upgrading of training and services of MDFCT). Baseline demographic characteristics, biochemical results, and outcomes of DFU in terms of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Only seven of the studies were included in the metaanalysis [25][26][27][28][29][30][31], as they reported the number of cases of LEA as well as the population denominator (not as rate) for both the intervention and control groups (either in parallel or before vs after). The results obtained from the meta-analysis are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only seven of the studies were included in the metaanalysis [25][26][27][28][29][30][31], as they reported the number of cases of LEA as well as the population denominator (not as rate) for both the intervention and control groups (either in parallel or before vs after). The results obtained from the meta-analysis are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [25][26][27][28] reported a decrease in the number of major LEAs while at the same time reporting either no difference or a slight increase in minor LEAs. Since data in these studies were aggregated, it was not possible to discern whether the increase in minor LEAs was due to multiple sequential minor amputations on the same patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] With the recent advent of the team approach to limb preservation, investigational and clinical efforts to promote an interprofessional approach to limb preservation are accelerating globally. [9][10][11][12][13][14][15] While podiatric and vascular surgery are indisputably key components to amputation prevention teams, 15 unnecessary amputations remain a substantial challenge and a correspondingly substantial team is required to meet this foe. Diabetes educators, endocrinologists, infectious disease specialists, interventional radiologists and cardiologists, nurses, pathologists, pedorthists, physical therapists, plastic surgeons, clinical scientists, and many others are valiantly working to save limbs.…”
mentioning
confidence: 99%